(untitled) (Research, Society and Development, 2020)
This study aims to verify the scientific productions made about intrafamily violence, what are its major emphases and how they are approached in these works. Thus, it was verified the number of publications in BVS Psicologia present, between 2004 and 2018, about the theme family violence, and its ramifications, in order to observe the importance that is given to this problem. In addition, we sought to analyze the understanding of violence that the publications presented, seeking to identify the repercussions of situations of violence for the family and the role of the psychologist in the face of the phenomenon. Therefore, the methodological approach adopted was the systematic review of bibliographies, also using the following descriptors: “intrafamily violence” and “psychology”. From this, the findings of this research revealed beyond the tiny psychological scientific production on intrafamily violence between 2004 and 2018, a high correlation of this category of violence with children and adolescents, showing a family scenario in which violent practices are found. Plenty of presents. Thus, the great urgency of rethinking family and parenting dynamics exercised by parents was concluded, as well as the importance of psychology in this scenario.